2018
DOI: 10.2224/sbp.7094
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Depression in Chinese Civil Servants

Abstract: We analyzed depression in Chinese civil servants, using the Hamilton Depression Rating Scale (HAMD) and a survey completed by people employed by the Civil Service in 6 cities in eastern China. The results showed that the HAMD is a valid and effective measure for assessing depression in Chinese civil servants. As we had assumed, Chinese civil servants manifested a strong sense of despair, which was consistent between the genders. In general, however, depression had a greater impact on female than on male civil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A large number of studies have shown that civil servants in various regions of China have different levels of anxiety, depression, burnout, and other psychological problems due to particular aspects of their work and environment (Li et al, 2013;Xu, Zhao, Wang, & Sun, 2010;Hao et al, 2014;Hao, Hong, Xu, Zhou, & Xie, 2015b). Ethnicity, resilience, and demographic characteristics are all considered to be factors affecting the mental health of civil servants (Fu et al, 2017;Hao et al, 2015b;Hong, Xie, Zhou, Hao, & Xu, 2015;Huang et al, 2018). Poor psychological flexibility is an important cause of many psychological and behavioral problems (Zhang, Wang, & Zhu, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that civil servants in various regions of China have different levels of anxiety, depression, burnout, and other psychological problems due to particular aspects of their work and environment (Li et al, 2013;Xu, Zhao, Wang, & Sun, 2010;Hao et al, 2014;Hao, Hong, Xu, Zhou, & Xie, 2015b). Ethnicity, resilience, and demographic characteristics are all considered to be factors affecting the mental health of civil servants (Fu et al, 2017;Hao et al, 2015b;Hong, Xie, Zhou, Hao, & Xu, 2015;Huang et al, 2018). Poor psychological flexibility is an important cause of many psychological and behavioral problems (Zhang, Wang, & Zhu, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many questionnaires have been used to measure mental health symptoms of Chinese civil servants, such as the Hamilton Depression Rating Scale (HAMD; Huang, Cao, Liu, Yao, & Rui, 2018), the twelve-item Short Form Health Survey (SF-12; Lu & Liang, 2016), the General Health Questionnaire (GHQ-12; Liang, Wang, & Yin, 2016), the Symptom Checklist 90 (SCL-90, Zhu et al, 2014), and the Civil Servants Stress Scale (CSSS, Hao et al, 2015a). However, no studies have measured the psychological flexibility of them.…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…A large number of studies have shown that civil servants in various regions of China have different levels of anxiety, depression, burnout, and other psychological problems due to particular aspects of their work and environment (Li et al, 2013;Xu, Zhao, Wang, & Sun, 2010;Hao et al, 2014;Hao, Hong, Xu, Zhou, & Xie, 2015b). Ethnicity, resilience, and demographic characteristics are all considered to be factors affecting the mental health of civil servants (Fu et al, 2017;Hao et al, 2015b;Hong, Xie, Zhou, Hao, & Xu, 2015;Huang et al, 2018). Poor psychological flexibility is an important cause of many psychological and behavioral problems (Zhang, Wang, & Zhu, 2012).…”
Section: Discussionmentioning
confidence: 99%